Effect of adding single-joint exercises to a multi-joint exercise resistance-training program on strength and hypertrophy in untrained subjects - Gentil, Paulo; Soares, Saulo Rodrigo Sampaio; Pereira, Maria Claúdia; Cunha, Rafael Rodrigues da; Martorelli, Saulo Santos; Martorelli, André Santos; Bottaro, Martim (Applied physiology, nutrition, and metabolism, 2013)
The aim of this study was to examine the effect of adding single-joint (SJ) exercises to a multi-joint (MJ) exercise resistance-training program on upper body muscle size and strength. Twenty-nine untrained young men participated in a 10-week training session. They were randomly divided in 2 groups: the MJ group performed only MJ exercises (lat pulldown and bench press); the MJ+SJ group performed the same MJ exercises plus SJ exercises (lat pulldown, bench press, elbow flexion, and elbow extension). Before and after the training period, the muscle thickness (MT) of the elbow flexors was measured with ultrasound, and peak torque (PT) was measured with an isokinetic dynamometer. There was a significant (p < 0.05) increase in MT (6.5% for MJ and 7.04% for MJ+SJ) and PT (10.40% for MJ and 12.85% for MJ+SJ) in both groups, but there were no between-group differences. Therefore, this study showed that the inclusion of SJ exercises in a MJ exercise training program resulted in no additional benefits in terms of muscle size or strength gains in untrained young men.